2007
DOI: 10.1111/j.1349-7006.2007.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression of T cell‐mediated immunity reduces sulfadimethoxine‐induced capsular inflammation and inhibits associated development of invasive thyroid follicular cell carcinomas in rats

Abstract: We previously demonstrated that thyroid capsular inflammation induced by continuous treatment with the antithyroidal agent sulfadimethoxine is associated with development of invasive follicular cell carcinomas in rats initiated with N-bis(2-hydroxypropyl)nitrosamine (DHPN). The inflammatory changes are characterized by large numbers of macrophages and lymphocytes as well as fibroblasts and we hypothesized that it might be enhanced by interplay between macrophages and T cells. To clarify this hypothesis, a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Migration of follicular epithelium from disrupted follicles into capsules was demonstrated at 4–6 weeks after the start of SDM treatment in rats initiated with DHPN in our previous experiments conducted under the same protocol as the present one, but their biological significance is uncertain. ( 13,14,25 ) Again in the present study, migrating cells were frequently observed, but they appeared to lack iNOS expression. On the other hand, immunoreactivity for iNOS was observed in carcinoma cells in invasive carcinomas, in which diffuse nuclear positivity for ssDNA was also demonstrated.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Migration of follicular epithelium from disrupted follicles into capsules was demonstrated at 4–6 weeks after the start of SDM treatment in rats initiated with DHPN in our previous experiments conducted under the same protocol as the present one, but their biological significance is uncertain. ( 13,14,25 ) Again in the present study, migrating cells were frequently observed, but they appeared to lack iNOS expression. On the other hand, immunoreactivity for iNOS was observed in carcinoma cells in invasive carcinomas, in which diffuse nuclear positivity for ssDNA was also demonstrated.…”
Section: Discussionsupporting
confidence: 55%
“…(19) In addition, follicular carcinomas were discriminated as intrathyroidal and invasive carcinomas involving the thyroid capsular and/or extrathyroidal tissues. (14) Immunohistochemical staining. Anti-rat CD3 antibody for T-cell surface antigen (clone G4.18, diluted at 1/500) and anti-mouse iNOS (clone 6, 1/200) were purchased from BD Biosciences (San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Promotion with propylthiouracil, another anti-thyroid agent that is less potent for inducing capsular inXammation than SDM, produces less frequent capsular invasive tumors, in parallel with weak capsular inXammation and Wbrosis (Imai et al 2005). Imai et al (2007) suggested that development of invasive carcinomas in the present model is enhanced by capsular inXammation mediated by T cells, and inducible nitric oxide synthase induction in the inXamed lesions may play a role in tumor progression. Thus, although neoplastic cell invasion itself can trigger Wbrous reactions, Wbrotic tissue formed during the capsular inXammation may provide the place of neoplastic cell invasion in response to inXammatory reactions.…”
Section: Discussionmentioning
confidence: 89%
“…Rats were given a single injection of the thyroid carcinogen, N-bis(2-hydroxypropyl) nitrosamine (DHPN), and then treated with an anti-thyroid agent, sulfadimethoxine (SDM), during the promotion stage. Although the role of inXammatory cell responses in capsular invasion was investigated in this model (Imai et al 2005(Imai et al , 2007, cellular signaling in the neoplastic cells responsible for this invasion was not.…”
Section: Introductionmentioning
confidence: 99%